Audit guide - Hayward, Stoy; Stoy Hayward & Co. (London : Butterworths, 1991)
The second edition of this book on litigation and financial assessment offers guidance on litigation support and covers recent major cases affecting claims for damages, reflecting the Courts' attitudes to damage assessment and changes in the duty of care for professionals and auditors.
Includes index.
oif 18/03/15
Loan
Keywords: Auditing; Auditing guide